Finite element analysis on bending of thin-walled structures using ANSYS - Toh, Han Wei (2014)
This project aims to develop a standard design procedure to simulate the bending behavior of thin-walled structures using finite element analysis (FEA). The developed procedure would be able to determine conservative predictions of the ultimate bending moment of the structures. The FEA program used for this study was ANSYS (academic version 14.0). In the first part of this project, the design procedures to simulate the buckling and post-buckling behavior of thin-walled structures using FEA developed by past studies were validated. Some analyses of a recurring problem, named as the “long column problem”, were also performed. As recommended by the previous study, the retrieval and organization of the FEA results was automated by developing a macro in Microsoft Excel. The second part of this project was to develop similar design procedures but focusing on the bending of the structures. To validate the robustness of the design procedure, specimens of two different cross sections were tested in this study, namely the plain channel and the hat section. The results obtained were validated against experimental data and led to the development of design procedures for the plain and hat sections.